Anti-inflammatory effect of chamomile from randomized clinical trials: a systematic review and meta-analyses - Jason Valmy; Stephanie Greenfield; Satoru Shindo; Toshihisa Kawai; Jorge Cervantes; Bo-Young Hong (Pharmaceutical Biology)
Context Chamomile is a widely recognized medicinal herb, and it has been used for its various medicinal properties. Chamomile’s widespread recognition and application in medicine highlights its significance in herbal therapeutic practices globally.Objective To explore chamomile as a low-risk antimicrobial and anti-inflammatory agent, utilizing clinical characteristics derived from the existing body of evidence from randomized clinical trials within the current literature.Methods We conducted a systematic review of randomized clinical trials using the search terms ‘chamomile anti-inflammatory antimicrobial randomized clinical trials’ and ‘chamomile anti-inflammatory antimicrobial’. We sourced data from databases including PubMed, Google Scholar, Cochrane Library, and ClinicalTrials.gov. We then performed a meta-analysis using R to assess the efficacy of chamomile as an anti-inflammatory and an antimicrobial agent, and its impact on mucosal recovery in clinical settings.Results A total of 11 randomized clinical trials were identified. The mean difference, confidence intervals, and standard error from the extracted means and standard deviations for relevant outcomes were calculated. Statistical tests from the meta-analysis demonstrated that chamomile exhibited statistically significant reductions in mucositis severity and pain level, indicating the anti-inflammatory effects of chamomile.Conclusion This study highlights chamomile’s potential as a natural alternative for managing inflammation and microbial infections, offering a promising alternative to standard treatments. Our study suggests chamomile has the potential to act as a natural anti-inflammatory agent. A future study with a larger sample size may provide clinical evidence of this effect.Systematic review registration number (PROSPERO): CRD42024566615